2017
DOI: 10.1111/1365-2435.12871
|View full text |Cite
|
Sign up to set email alerts
|

High suckling rates and acoustic crypsis of humpback whale neonates maximise potential for mother–calf energy transfer

Abstract: Summary The migration of humpback whales to and from their breeding grounds results in a short, critical time period during which neonatal calves must acquire sufficient energy via suckling from their fasting mothers to survive the long return journey. Understanding neonate suckling behaviour is critical for understanding the energetics and evolution of humpback whale migratory behaviour and for informing conservation efforts, but despite its importance, very little is known about the details, rate and behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 66 publications
(117 reference statements)
8
80
1
Order By: Relevance
“…Both Zoidis & Lomac-MacNair (2017) and Videsen et al (2017) concluded that in the breeding grounds mother-calf pairs remained mostly stationary while nursing, and Videsen et al (2017) additionally concluded that nursing only occurred during the ''bottom phase'' of dives (similar to the term ''horizontal phase'' used in this study). Contrary to these findings, nursing on the feeding grounds during our study occurred while the pair was moving and during descending, ascending, and horizontal phases of dives.…”
Section: Nursing Duration Frequency and Depthsupporting
confidence: 56%
See 4 more Smart Citations
“…Both Zoidis & Lomac-MacNair (2017) and Videsen et al (2017) concluded that in the breeding grounds mother-calf pairs remained mostly stationary while nursing, and Videsen et al (2017) additionally concluded that nursing only occurred during the ''bottom phase'' of dives (similar to the term ''horizontal phase'' used in this study). Contrary to these findings, nursing on the feeding grounds during our study occurred while the pair was moving and during descending, ascending, and horizontal phases of dives.…”
Section: Nursing Duration Frequency and Depthsupporting
confidence: 56%
“…Another study in the breeding grounds used archival motion-sensing tags to study suckling behavior; however, since actual nursing could not be visually verified, Videsen et al (2017) inferred suckling dives and active dives based on a 1.5 m/s 2 median trimmed and normalized minimum specific acceleration (MSA) threshold value determined by surface observations of peduncle dives (Gero & Whitehead, 2007). Therefore, we were restricted in our ability to compare the kinematic values of our ''nursing events'' to Videsen et al (2017) ''suckling dives'' because ''suckling dives'' by definition only included periods of low MSA values.…”
Section: Nursing Duration Frequency and Depthmentioning
confidence: 99%
See 3 more Smart Citations